Establishment and validation of a nomogram containing cytokeratin fragment antigen 21-1 for the differential diagnosis of intrahepatic cholangiocarcinoma and hepatocellular carcinoma - Liu, Yuan-Yuan; Li, Yue-Yue; Liu, Yong-Shuai; Zhang, Zong-Li; Gao, Yan-Jing (Frontiers in Oncology, 2024)
Background: Our study aimed to develop a nomogram incorporating cytokeratin fragment antigen 21-1 (CYFRA21-1) to assist in differentiating between patients with intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC).: A total of 487 patients who were diagnosed with ICC and HCC at Qilu Hospital of Shandong University were included in this study. The patients were divided into a training cohort and a validation cohort based on whether the data collection was retrospective or prospective. Univariate and multivariate analyses were employed to select variables for the nomogram. The discrimination and calibration of the nomogram were evaluated using the area under the receiver operating characteristic curve (AUC) and calibration plots. Decision curve analysis (DCA) was used to assess the nomogram's net benefits at various threshold probabilities. Results: Six variables, including CYFRA21-1, were incorporated to establish the nomogram. Its satisfactory discriminative ability was indicated by the AUC (0.972 for the training cohort, 0.994 for the validation cohort), sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) values. The Hosmer-Lemeshow test and the calibration plots demonstrated favorable consistency between the nomogram predictions and the actual observations. Moreover, DCA revealed the clinical utility and superior discriminative ability of the nomogram compared to the model without CYFRA21-1 and the model consisting of the logarithm of alpha-fetoprotein (Log AFP) and the logarithm of carbohydrate antigen 19-9 (Log CA19-9). Additionally, the AUC values suggested that the discriminative ability of Log CYFRA21-1 was greater than that of the other variables used as diagnostic biomarkers. Conclusions: This study developed and validated a nomogram including CYFRA21-1, which can aid clinicians in the differential diagnosis of ICC and HCC patients.